The Comparison between Tree Sorrel and Snake Plant on the Hatchability Inhibition of Apple Snail Eggs - Fatimatuzzahra, Fatimatuzzahra; Putriana, Adetha; Jumadi, Jemmy; Lestari, Dian Fita; Anggoro, Bambang Sri (Biosfer: Jurnal Tadris Biologi, 2020)
This study aimed to compare and determine the hatchability inhibition of the tree sorrel extract (Averrhoa bilimbi L.) and snake plant as natural ovicide of apple snail (Pomacea canaliculata L.). This study employed the completely randomized design (CRD). The negative controls were the extracts with the concentrations of 1%, 1.5%, 2%, 2.5%, 3%, and a positive control. Data analysis used was one-way ANOVA and then continued by Least Significant Difference (LSD) test. The results showed that tree sorrel extract with 3% concentration had the highest inhibitory on the hatchability of apple snail eggs compared to the snake plant extract (Sansevieria trifasciata P.) with a comparison value of 19.47%. Perbandingandaya Hambat Tetas Telur Keong Mas dari Buah Belimbing Wuluh dan Daun Lidah MertuaAbstrak: Tujuan penelitian ini untuk membandingkan dan mengetahui daya hambat tetas telur keong mas dari ekstrak buah belimbing wuluh (Averrhoa bilimbi L.) dan daun lidah mertua sebagai ovisida alami keong mas (Pomacea canaliculata L.). Desain penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan konsentrasi yaitu kontrol negatif, 1%, 1,5%, 2%, 2,5%, 3% dan kontrol positif. Analisis data menggunakan uji One Way Anova dilanjutkan dengan ujiBeda NyataTerkecil (BNT). Hasil penelitian menunjukkan bahwa ekstrak buah belimbing wuluh dengan konsentrasi 3% mempunyai daya hambat tertinggi terhadap penetasan telur keong mas dibandingkan ekstrak daun lidah mertua (Sansevieria trifasciata P.), yaitu sebesar 19,47%.